PKM PASCA PANEN UBI JALAR UNGU DAN OLAHANNYA BAGI SISWA SISWI NEGERI 1 BAWEN SEMARANG - Sagitaning Putri, Aldila; Larasati, Dewi; Sani, Elly Yuniarti (STAI Darul Qalam Tangerang, 2023)
Students of SMK Negeri 1 Bawen in gaining knowledge about postharvest handling and horticultural preparations are only given in general for horticultural crops and practicum given only certain fruits, so that postharvest handling and purple sweet potato preparations have not been given specifically. This community service activity aims to: Provide information to the community, especially at SMK Negeri 1 Bawen Semarang Regency, about the importance of handling purple sweet potato postharvest and how to process it and provide skills in processing purple sweet potatoes into purple rice and purple sweet potato ice cream. The target audience in community service is students of SMK Negeri 1 Bawen Semarang Regency who are in accordance with the Department of Agricultural Product Technology. The results of the implementation showed that the target was students of SMK Negeri 1 Bawen increased their knowledge and understanding of the importance of post-harvest handling and tomato processing with practice. This is based on questions and answers, interviews and questionnaires distributed before and after the activity. The evaluation was carried out using questionnaires before and after the implementation given to 70 participants who participated. The results of the evaluation show that: a. Before the implementation of the activity, 80% of participants had never received counseling on post-harvest handling, b. Before the implementation 75% did not know about the processing of purple sweet potatoes and 25% knew, after the implementation 85% knew and 20.67% knew very much about the processing of purple sweet potatoes, c. 100% of participants did not know about processing purple sweet potatoes into purple rice and after counseling 3.33% did not know, 96.67% knew and 10% knew very well, d. 100% of extension participants did not know how to process purple sweet potatoes into ice cream and after counseling 86.67% knew and 13.33% knew how to process purple sweet potato becomes ice cream, e. Knowledge of the benefits of purple sweet potatoes of extension participants before the activity 66.7% did not know, 33.33% knew and 6.67% knew very well, and after the activity 73.33% knew and 26.66% knew very well, and f. Knowledge of processed purple sweet potatoes in addition to being purple rice and purple sweet potato ice ream states 100% tofu